The tectonic and metallogenic framework of Myanmar: A Tethyan mineral system - Nicholas J. Gardiner (2018)
© 2016 Elsevier B.V. Myanmar is perhaps one of the world's most prospective but least explored minerals jurisdictions, containing important known deposits of tin, tungsten, copper, gold, zinc, lead, nickel, silver, jade and gemstones. A scarcity of recent geological mapping available in published form, coupled with an unfavourable political climate, has resulted in the fact that, although characterized by several world-class deposits, the nation's mineral resource sector is underdeveloped. As well as representing a potential new search space for a range of commodities, many of Myanmar's known existing mineral deposits remain highly prospective. Myanmar lies at a crucial geologic juncture, immediately south of the Eastern Himalayan Syntaxis, however it remains geologically enigmatic. Its Mesozoic-Recent geological history is dominated by several orogenic events representing the closing of the Tethys Ocean. We present new zircon U-Pb age data related to several styles of mineralization within Myanmar. We outline a tectonic model for Myanmar from the Late Cretaceous onwards, and document nine major mineralization styles representing a range of commodities found within the country. We propose a metallogenetic model that places the genesis of many of these metallotects within the framework of the subduction and suturing of Neo-Tethys and the subsequent Himalayan Orogeny. Temporal overlap of favourable conditions for the formation of particular deposit types during orogenic progression permits the genesis of differing metallotects during the same orogenic event. We suggest the evolution of these favourable conditions and resulting genesis of much of Myanmar's mineral deposits, represents a single, evolving, mineral system: the subduction and suturing of Neo-Tethys.